Chemical characterization of unconventional palm oils from Hyophorbe indica and two other endemic Arecaceae species from Reunion Island. Issue 1 (2nd January 2020) - Caro, Yanis; Petit, Thomas; Grondin, Isabelle; Clerc, Patricia; Thomas, Hermann; Giuffrida, Daniele; Giocastro, Barbara; Tranchida, Peter Q.; Aloisi, Ivan; Murador, Daniella; Mondello, Luigi; Dufossé, Laurent
Abstract: Chemical characteristics of novel seed oils, yet not investigated, from three endemic Arecaceae (palm) species from Reunion Island are described. Fatty acid profiles are performed using two-dimensional gas chromatography-mass spectrometry. Carotenoid contents are determined by high performance liquid chromatography-mass spectrometry. The results of the investigations emphasize the particular composition of the unconventional red seed oil from Hyophorbe indica . Characteristic features of this oil reveal a high degree of unsaturation (50% of polyunsaturated fatty acids, with a high content (17%) of omega-3), which is possibly a unique fatty acid composition in the Arecaceae family. The two other palm oils from Dictyosperma album and Latania lontaroides contain high level of saturated fatty acids very similar to that of the edible palm oil. H. indica oil is also very rich in valuable carotenoids; in particular, lutein, β-carotene and lycopene are detected in a high content (respectively 45, 23 and 35 mg.kg −1 in oil). Graphical Abstract: